A general strategy for the preparation of aligned multiwalled carbon nanotube/inorganic nanocomposites and aligned nanostructures. (January 2015) - Ji, Lijun; Wang, Wenjun; Stevens, Molly M.; Zhou, Songtao; Zhu, Aiping; Liang, Ji
Graphical abstract: A general strategy for the preparation of aligned structures including aligned nanotubes, nanofibers, and multiwalled carbon nanotubes (AMWCNTs)/inorganic nanocomposites was realized by synthesizing inorganic materials within an effective AMWCNTs/hydrogel composite template. Chemical reactions, which could damage the graphitic and aligned structures of AMWCNTs, are not necessary in this strategy. Abstract: A general strategy for the preparation of aligned multi-walled carbon nanotube (AMWCNT)/inorganic composites and aligned nanostructures was realized by synthesizing materials within an AMWCNT/hydrogel composite template. Chemical reactions that could damage the AMWCNT structure are not necessary in this strategy. AMWCNT composites of many materials were synthesized. Three typical and popularly used materials were present to show the versatility of the strategy: hydroxyapatite, alumina, and silver. The morphologies of the materials formed on the nanotube surface include continuous layers, nanoparticles, and microspheres. The structures formed after the removal of AMWCNTs include aligned nanofibers, aligned nanotubes, and particles.